The Role of E-Banking on the Switching Behaviour of Retail Clients of Commercial Banks in Polokwane, South Africa - Masocha, Reginald; Matiza, Tafadzwa (Journal of Economics and Behavioral Studies, 2017)
This study focused on investigating the role of E-banking on the switching behaviour of retail bank clients in Polokwane, South Africa. Recently, studies have shown that people are switching banks more often than in the past. Circumstances that are beyond control cause people to switch. This has become a challenge in the banking industry as many banks lose their clients. However, newly developed technologies have brought many changes in the operation of banks. The new E-banking services have enabled bank clients to have access to their bank account for 24 hours without visiting the physical branch. A sample of 98 respondents was surveyed in Polokwane, South Africa using the convenience sampling technique. The cronbach alpha test was used to ascertain reliability of the findings. The findings reveal that demographic characteristics have much impact on the switching behaviour of commercial bank clients and acceptance of e-banking services. Switching factors such as bank charges, low interest rates on savings, promotion activities, location and switching costs were the major reasons for bank customers to switch banks.